Knowledge and attitudes of residents regarding electroconvulsive therapy [Asistanların elektrokonvulsif tedavi ile ilgili bilgi ve tutumları] - (:unkn) unknown (Gulhane Military Medical Academy, 2015)
AIM: To determine the knowledge and attitudes of non-psychiatry residents about electroconvulsive therapy (ECT) and additionally to make a comparison between residents of medical sciences and surgical sciences. METHODS: The study consisted of 176 medical school graduates in their residency training (119 medical sciences, 57 surgical sciences) at a university hospital. All subjects are asked to fill a questionnaire prepared by the authors. RESULTS: Among all, 58 of the medical sciences residents (48.7%), and 32 of the surgical sciences residents (56.1%) had reported that they have never observed any ECT session. There was no statistically significant difference between the residents of the two groups in terms of theirs attitudes towards ECT (p>0.05). The residents of surgical sciences differed from the others only in their response to the question that sought answer whether they would agree to have any of their relatives to undergo ECT. They more often disagreed to this statement (p=0.02). CONCLUSIONS: The knowledge and attitudes of residents in medical, and surgical sciences about ECT seemed to be similar. Despite their significant amount of knowledge about ECT the residents showed similar attitudes towards it with the patients and their caregivers that were previously reported in the literature. Additionally, the results also suggest that current training in medical schools need a revision that would eventually improve attitudes of medical graduates towards ECT. © 2015, TAF Preventive Medicine Bulletin.
Keywords: Attitudes; Electroconvulsive therapy; Level of knowledge; Medical resident trainees